2013
DOI: 10.1175/jcli-d-12-00117.1
|View full text |Cite
|
Sign up to set email alerts
|

Interannual Climate Variability over the Tropical Pacific Ocean Induced by the Indian Ocean Dipole through the Indonesian Throughflow

Abstract: The authors’ previous dynamical study has suggested a link between the Indian and Pacific Ocean interannual climate variations through the transport variations of the Indonesian Throughflow. In this study, the consistency of this oceanic channel link with observations is investigated using correlation analyses of observed ocean temperature, sea surface height, and surface wind data. The analyses show significant lag correlations between the sea surface temperature anomalies (SSTA) in the southeastern tropical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
94
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(99 citation statements)
references
References 53 publications
5
94
0
Order By: Relevance
“…The enhanced transport leads to thermocline elevations that generate an upwelling Kelvin wave, which propagates to the eastern equatorial Pacifi c Ocean favoring anomalous cooling in the Pacifi c cold tongue with a one-year time lag. This oceanic channel dynamic has been supported by lag correlation analysis of observational data (Yuan et al, 2013). The results have shown signifi cant correlations between STIO SSTA or sea surface height anomalies (SSHA) in fall and SSTA, SSHA, and subsurface temperature anomalies in the central and eastern equatorial Pacifi c Ocean with a one-year time lag.…”
Section: Introductionmentioning
confidence: 67%
See 3 more Smart Citations
“…The enhanced transport leads to thermocline elevations that generate an upwelling Kelvin wave, which propagates to the eastern equatorial Pacifi c Ocean favoring anomalous cooling in the Pacifi c cold tongue with a one-year time lag. This oceanic channel dynamic has been supported by lag correlation analysis of observational data (Yuan et al, 2013). The results have shown signifi cant correlations between STIO SSTA or sea surface height anomalies (SSHA) in fall and SSTA, SSHA, and subsurface temperature anomalies in the central and eastern equatorial Pacifi c Ocean with a one-year time lag.…”
Section: Introductionmentioning
confidence: 67%
“…Studies have also suggested that IOD events can affect tropical Pacifi c sea surface temperature anomalies (SSTA) (Wu and Kirtman, 2004;Annamalai et al, 2005;Xie et al, 2009;Luo et al, 2010;Okomura and Deser, 2010). The mechanisms of IOD forcing on the equatorial Pacifi c have been attributed to the atmospheric bridge process through the Walker circulation (Ohba et al, 2010;Kug and Ham, 2012;Santoso et al, 2012), and/or to the oceanic channel dynamics through the Indonesian throughfl ow (ITF) (Yuan et al, 2011(Yuan et al, , 2013.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…From observational data it cannot be decided which mechanism is more relevant and in fact other mechanisms might also play a role, such as variability in the Indonesian Throughflow induced by SSH anomalies in the southeastern IO (Yuan et al 2011(Yuan et al , 2013. Modeling studies are necessary to disentangle cause and consequences, especially concerning influences on the WWV, and investigate important issues such as how the wind anomalies propagate from the IO to the PO on interannual time scales and how this might influence the burstiness.…”
Section: Summary Discussion and Conclusionmentioning
confidence: 99%